The spread of no-till in conservation agriculture systems in Italy: Indications for rural development policy-making - Danilo Marandola; Angelo Belliggiano; Luca Romagnoli; Corrado Ievoli (Agricultural and Food Economics, 2019)
No-tillage is a farming system aiming at minimizing soil disturbance associated with the cultivation of arable crops. This technique, together with the practices of continuous soil cover and of crop rotation, also represents one of the elements of the so called Conservation agriculture, a paradigm of sustainable agriculture that is spreading in many areas of the globe. The aim of the work is to examine the spread of No-tillage in Italy analyzing the modalities of adoption and the factors that can influence it. Modalities of adoption can vary depending on whether No-tillage represents an incremental innovation within the ordinary management of the farm, or a complementary element of an alternative technological paradigm identifiable with Conservation agriculture. Factors influencing the adoption of No-tillage, widely studied in the literature, concern the characteristics of the natural environment, the structural features of the holdings (i.e. size) and also the presence of knowledge spillovers that are largely the result of spatial networks between farmers and other stakeholders. Elaborations have been first of all aimed at distinguishing the two types of modalities of adoption and subsequently at verifying the influence of the factors mentioned above, in particular through the Local Moran Index. In summary, the work describes how the diffusion of No-tillage practices can be partly ascribed to a cost saving-oriented incremental innovation process in the framework of a conventional paradigm of agriculture that mainly pertain to large size holdings. However, there is a significant number of farms where the adoption of No-tillage practices demonstrates the decision to try a more comprehensive reorganization of the way of doing agriculture, similar to the paradigm of Conservation agriculture, and in which the cognitive and relational aspects related to the aforementioned networks seem to be very important. Spatial analysis has allowed to depict two models of adaptation to the paradigm of Conservation agriculture: one is mainly concentrated in the rural areas of the central-northern Apennines, and another is located mainly in two regions of southern Italy (Puglia and Sicily).
Keywords: 330; No-tillage; Conservation agriculture; Networks; Rural development policy